Morphometric analysis of Gorontalo (Indonesia) native chickens from six different regions - ALFI SOPHIAN; ABINAWANTO ABINAWANTO; UPI CHAIRUN NISA; FADHILLAH FADHILLAH (Society for Indonesian Biodiversity, 2021)
Abstract. Sophian A, Abinawanto, Nisa UC, Fadhillah. 2021. Morphometric analysis of Gorontalo (Indonesia) native chickens from six different regions. Biodiversitas 22: 1757-1763. Research on the diversity of Gorontalo native chickens based on morphometric analysis of body weight, leg length, head length, head length to beak and head width was conducted. This study was conducted to identify the diversity of native chickens in six regions spread across Gorontalo Province, Indonesia. The method used in conducting statistical analysis is the principal component analysis (PCA) method. This method was performed to identify which morphometric factors play a role in relationship analysis of Gorontalo native chickens. Based on statistical analysis, it was found that of the 5 variables used in this study, 3 variables had Measure of Sampling Adequacy (MSA) values > 0.5 ranged from 0.537 to 0.648, namely body weight, leg length, and head length. Meanwhile, the other 2 variables, namely Head to Beak Length and Head Width, have MSA values <0.5 with values of 0.313 and 0.316. This causes the other 2 variables to be used as a differentiating variable in analyzing the relationship between native chickens from six different regions scattered in the Gorontalo Province. The morphometric analysis of body weight means that the chickens sampled from Boalemo were morphometrically the largest in size, while the chickens sampled from Pohuwato were morphometrically the smallest. Chickens sampled from North Gorontalo, Bone Bolango, and Gorontalo City tended to be more uniform when compared to the chickens sampled from Pohuwato and Boalemo areas, while for Gorontalo District it was larger in size than Pohuwato, North Gorontalo, Bone Bolango, and Gorontalo City, but smaller than Boalemo.